The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fimmu.2022.865773
|View full text |Cite
|
Sign up to set email alerts
|

GATA 2 Deficiency: Focus on Immune System Impairment

Abstract: GATA2 deficiency is a disease with a broad spectrum of clinical presentation, ranging from lymphedema, deafness, pulmonary dysfunction to miscarriage and urogenital anomalies, but it is mainly recognized as an immune system and bone marrow disorder. It is caused by various heterozygous mutations in the GATA2 gene, encoding for a zinc finger transcription factor with a key role for the development and maintenance of a pool of hematopoietic stem cells; notably, most of these mutations arise de novo. Patients car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 55 publications
(91 reference statements)
0
7
0
Order By: Relevance
“…The evolution of cytopenias in GATA2 deficiency syndrome has been described using symptomatic patients with DCML deficiency, and even though T cell cytopenias have been described, the profound and persistent T cell lymphopenia from birth in our patient is unusual and to our knowledge this early finding has not been described in GATA2 deficiency before (3,7,8). It is unclear if this presentation is simply a variable presentation of GATA2 deficiency, or if there are other genetic modifiers that may have affected these results.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The evolution of cytopenias in GATA2 deficiency syndrome has been described using symptomatic patients with DCML deficiency, and even though T cell cytopenias have been described, the profound and persistent T cell lymphopenia from birth in our patient is unusual and to our knowledge this early finding has not been described in GATA2 deficiency before (3,7,8). It is unclear if this presentation is simply a variable presentation of GATA2 deficiency, or if there are other genetic modifiers that may have affected these results.…”
Section: Discussionmentioning
confidence: 66%
“…Of the 6 GATA proteins, GATA1 and GATA2 play critical roles in hematopoiesis with GATA2 being a key transcriptional regulator required for the development and maintenance of a healthy stem cell pool (4,5). Hematological manifestations of GATA2 deficiency include a range of peripheral cytopenias of which the most common are profound cytopenias of B-cells, NK cells, and monocytes, that tend to be progressive with loss of bone marrow progenitor populations over time and a tendency toward clonal hematopoiesis (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Meggendorfer et al concluded that mutations in GATA2 , ASXL1 , IDH2 , RUNX1 , NRAS , SRSF2 , and ETV6 genes might predispose a transformation to leukemia [ 23 ]. It was observed that MDS cases with GATA2 mutation presented cytogenetic aberrations: the most frequent were chromosome 7 anomalies such as monosomy 7 and der (7) in 41% of investigated patients, followed by the gain of chromosome 8 (trisomy 8) in 15% of patients, while complex karyotype and deletion 5q were very rare or absent [ 68 ].…”
Section: Molecular Signaturementioning
confidence: 99%
“…However, bone marrow dysfunction represents the hallmark of the disease, leading to recurrent infections (mainly atypical mycobacterial infections and recurrent HPV-related warts) and hematological malignancies. 47 49 Patients carry loss-of-functions mutations, involving mostly the second zinc finger domain and resulting in GATA2 haploinsufficiency. 50 GATA2 deficiency underlies 15% of advanced forms and 7% of all primary MDS in childhood.…”
Section: Hematologic Neoplasms With Germline Predisposition Associate...mentioning
confidence: 99%